The Effect of Hospital Service Management on Outpatient Satisfaction among BPJS Health Insurance Participants at Amri Tambunan Regional General Hospital - Ramadhani Syafitri Nasution; Setia Megawati Hutaju; Meriahta Sitepu (Universitas Ibn Khaldun Bogor, 2026)
Patient satisfaction is an important indicator of the quality of healthcare services, particularly among participants of Indonesia's National Health Insurance (BPJS Health). This study aimed to analyze the effect of hospital service management functions planning, organizing, implementation, and controlling—on outpatient satisfaction among BPJS Health participants at Amri Tambunan Regional General Hospital. A quantitative study with a cross-sectional design was conducted involving 100 respondents selected using an accidental sampling technique. Data were collected through a structured questionnaire that had been tested for validity and reliability. The data were analyzed using multiple logistic regression. The results showed that all four hospital service management functions had a significant effect on outpatient satisfaction (p < 0.05). Among these variables, service implementation was identified as the most dominant factor influencing patient satisfaction, with an Odds Ratio (OR) of 445.949. This finding indicates that service delivery characterized by adherence to procedures, promptness, responsiveness, and effective communication plays a crucial role in improving patient satisfaction. The study concludes that effective hospital service management, supported by well-organized planning, coordination, implementation, and supervision, is essential for enhancing the quality of outpatient services. Therefore, strengthening the implementation and organizational aspects of hospital service management should be prioritized to improve patient satisfaction among BPJS Health participants at Amri Tambunan Regional General Hospital.